Suppose 2*v - 3 = v. Suppose 4*g - 16 = -4*q, 1 = g - 2*q + 6. Suppose 3 - g = 2*a. Solve v*i - 4*i = -a for i.
1
Let d(p) = 32*p3 + 2*p - 1. Let b be d(1). Suppose -b - 67 = -5*t. Let z(l) = 2*l2 - l + 2. Let w be z(2). Solve w = 4*f + t for f.
-3
Let j = 27 - 14. Solve -28 = -3*c - j for c.
5
Let y be 1 - (5 + -1 + 2). Let q be 2⁄5 + (-73)/y. Suppose j = -2*j + q. Solve j*r - 8 = -28 for r.
-4
Let n be 6/(15⁄6 - 1). Solve -n*f + 10 = -2*f for f.
5
Let c(s) = 3*s - 2. Let q be c(2). Suppose q*l - 2*v - 2*v = 12, -4 = -v. Suppose -5*m + 8 + l = 0. Solve 0 = 3*z - 12 - m for z.
5
Let r(s) = -s - 1. Let p be r(6). Let y = p - -7. Solve -5*k = -y - 20 for k.
4
Let s(w) = w**2 + 9*w. Suppose m = 5*m + 36. Let p be s(m). Solve -5*h - 21 - 4 = p for h.
-5
Let v(j) = j**2 - 4. Let k be v(-3). Suppose -22 = -4*q - k*c, 5*q - 2*c - 25 = -7*c. Solve -10 = q*h + 5 for h.
-5
Let t be (-4)/(-14) - (-19)/7. Suppose -t*q + 18 = -q. Let x = q - 5. Solve -x*g + 7 = -5 for g.
3